Serum Copper in Anemic Patients - Huma AbdulShakoor , Kashif Jamil, Samina T.Amanat , Farhat Waqar , Waseem Yawar , Masooma Raza (Journal of Rawalpindi Medical College, 2014)
Background : To analyze serum copper in anemic patients. Method: In this descriptive study, serum samples of 136 anaemic patients were collected. Patients taking copper and zinc supplements, on parenteral nutrition, with acute blood loss, with malignant haematological disorders and children of less than 1 year of age were not included. Five ml of venous blood samples were collected in vacutainers, without anticoagulant.Serum was aliquoted into labelled appondrof tubes and stored in freezer at -80° C. Samples were transported to Chemical analysis facility division(CAFD) maintaining cold chain. Serum copper levels were determined by atomic absorption spectrophotometry. Results: Out of 136, majority (80.88%) were female, with male to female ratio of 1:4.2. The age of the patients ranged from 1 to 79 years. Maximum patients were in 21-30 years age group. Copper deficiency was found in 17.64%, while 19.85% had raised levels. Microcytic anaemia was predominant. Majority (68.38%) had moderate anaemia. Most of the patients with decreased or increased copper levels fell into moderate anaemia . In addition to anaemia, 9.56% had bicytopenia and 5.14% had pancytopenia. Conclusion Both copper excess and deficiency were noted in this study. Though copper as cause of anemia may be rare, but it may have some contributory role in anaemia.